Fine manipulation of terahertz waves via all-silicon metasurfaces with an independent amplitude and phase. Issue 11 (12th March 2021) - Zheng, Chenglong; Li, Jie; Wang, Guocui; Wang, Silei; Li, Jitao; Zhao, Hongliang; Zang, Huaping; Zhang, Yan; Zhang, Yating; Yao, Jianquan
Abstract : All-silicon metasurfaces are proposed to achieve multifunctional designs and simultaneous modulation of amplitude and phase profiles. This approach for generating an editable amplitude and phase may pave a way to design ultra-thin photonic devices. Abstract : Integrating independent wavefront controls into one device can meet the increasing demand for high-capacity flat electromagnetic devices. Simultaneously and independently controlling the amplitude and phase is pivotal for completely manipulating the propagation of electromagnetic waves. Here, we propose several all-silicon metasurfaces to achieve multifunctional designs and simultaneous modulation of amplitude and phase profiles in the terahertz (THz) band. These metasurfaces integrate two degrees of freedom of the propagation phase and Pancharatnam-Berry (PB) phase. To illustrate the feasibility of this design, three schematic functions are shown below: a three-channel vortex beam generator, a controllable intensity ratio of co- and cross-polarizations corresponding to the incident circular polarization (CP), and a bifocal metasurface that is capable of generating two off-axis vortices with controllable power allocation. A sample is fabricated to specifically verify the amplitude and phase modulation of this design. The experimental results agree well with the simulations and validate the good performances of our proposals. This approach for directly generating an editable amplitude and phase may provide a new choice to design ultra-thin photonic devices.